Nutritional Quality and Safety of Complementary Foods Developed from Blends of Staple Grains and Honey Bee Larvae (Apis mellifera) - Shewangzaw Addisu Mekuria; John N. Kinyuru; Beatrice Kiage Mokua; Mesfin Wogayehu Tenagashaw (International Journal of Food Science)
Complementary foods must be adequate to satisfy the nutritional needs of the growing child together with breastfeeding. This study was aimed at evaluating the nutritional composition, microbial safety, and sensory quality of extruded complementary foods developed from blends of staple grains and insect bee larva (Apis mellifera). Teff, maize, soybean, and bee larva samples were milled to flour and blended before extrusion as follows: ComF01 (57% maize, 29% teff, and 14% soybean) and ComF02 (58% maize, 29% teff, and 13% bee larvae) using NutriSurvey software (version, 2007). Nutrient composition, microbial, and sensory analyses of developed flour blends were conducted using standard methods. The proximate composition of moisture, fat, fiber, carbohydrate, and energy was significantly different between the developed and commercial wean-mix foods. ComF02 recorded the highest fat content (14.3 g/100 g), energy (427.18 kcal/100 g), and vitamins A (706 μg/100 g), B3 (8.2 mg/100 g), and B9 (86.7 mg/100 g) while ComF01 had the highest protein content (12.56 g/100 g). Iron (40.94 mg/100 g) and calcium (68.20 mg/100 g) were the minerals with the highest content in ComF02. Both ComF01 and ComF02 met the recommended dietary allowance of nutrients for infants aged 6-12 months. Overall, the present study showed that bee larvae can be used to develop complementary foods that are nutritionally adequate, microbiologically safe, and sensory acceptable meeting the dietary allowance of infants at an acceptable level compared to conventional cereal-based foods.